Intensitas Serangan Jamur Ganoderma sp Pada Perkebunan Kelapa Sawit Lahan Mineral dan Lahan Pasang Surut - Rahmana, Billy Aditia; Hayata, Hayata; Hartawan, Rudi (Jurnal Media Pertanian, 2024)
Stem rot disease caused by fungus (Ganoderma sp)  is a major challenge in oil palm farming. This fungus infects oil palm trees at every stage of growth. This disease has a gradualy development, which the symptoms only appearing in the last stages, so it is called as "silent killer" of oil palm trees. This study aims to determine the attacks intensity of Ganoderma sp fungus on oil palms planted in mineral land and tidal land. This research was conducted on mineral land in Suko Awin Jaya Village, Muaro Jambi Regency and tidal land in Petanang Kumpeh Village. This research was conducted in May - July 2024. The research was conducted under unformatted trial design. The research location was purposive chosen for there were relatively uniform plants in that location, and the Ganoderma sp attacks were found in that place namely:1. Mineral land, 2. Tidal land.  There were 2 sampling sites, in two different land, with an area of 1 Ha, which were randomly selected from 5 hectares of existing plants. Census sampling method was used to determination the trees as a sample at the research location so sample totaly were 135 trees. The results of this study showed that on mineral land the attacks percentation  was 2.61% and the attacks intensity  was 1.99% higher than the attacks percentation and attacks intensity on tidal land representative 1.50% and  1.13%.